British Association of Dermatologists guidelines for the management of lichen sclerosus, 2018. (18th April 2018) - Lewis, F.M.; Tatnall, F.M.; Velangi, S.S.; Bunker, C.B.; Kumar, A.; Brackenbury, F.; Mohd Mustapa, M.F.; Exton, L.S.
Summary: Lichen sclerosus (LS) is a chronic skin disease mainly affecting the anal and genital region. This article is a guideline, which means that the authors looked at all the available evidence about LS in scientific journals, and from this, put together up‐to‐date, evidence‐based recommendations for the management of the disease in adults (18+ years), children (0–12 years) and young people (13–17 years). The guideline was written by a committee of the British Association of Dermatologists, following strict criteria they have for assessing all the different studies on the subject. The guideline helps to guide doctors and nurses working in primary care (which means a patient's first port of call when they have a health problem, e.g. GP clinics, walk‐in centres) as well as in secondary care (meaning where GPs will send people for more specialist care, e.g. hospitals). The guideline covers a range of issues, from treatment options, to gaps in research that need to be addressed. From the guideline, an updated Patient Information Leaflet has been created and is available on the British Association of Dermatologists' website (www.bad.org.uk ). On the basis of these studies and expert consensus, 31 recommendations are made for the diagnosis and management of LS for both general practitioners and secondary care specialists. The recommended patient treatment pathways are presented as flow diagrams for men and women. All the evidence points to a potent topical steroid ointment as the most effective treatment for the condition. This is initially used for 3 months and then the frequency of treatment application is tailored to the individual patient to maintain good control of both symptoms and signs. Nine suggestions for future research studies are made to answer some outstanding questions and to fill gaps in current knowledge. Abstract : Linked Article:  Lewis et al. Br J Dermatol 2018; 178 :839–853